2022 Review of Adequacy of Poverty Reduction and Growth Trust Finances. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2022)
This paper provides the first review of the adequacy of PRGT finances since the comprehensive reform of the Poverty Reduction and Growth Trust (PRGT) in July 2021. It describes the lending response to the unprecedented pandemic-related demand; updates the PRGT demand scenarios and the estimates of the longer-term PRGT resource needs; reports on progress with the first stage of the two-stage PRGT funding strategy approved in July 2021; and outlines recent developments in the various debt relief initiatives and their status.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Money and Monetary Policy; Political Economy